MALE FEMINIST DI INDONESIA: TINJAUAN LITERATUR TENTANG PARTISIPASI, REPRESENTASI, DAN TANTANGANNYA - Rahmat Noferdy; Tience Debora Valentina (Jurnal Harkat : Media Komunikasi Gender, 2025)
Abstract. The feminist movement began with women's resistance to gender inequality, which in its development also involved the participation of men as male feminists. This study aims to examine the existence, development, forms of participation, and the meaning of male feminist involvement in Indonesia. This study used a literature review method on six selected articles from 2015-2024 obtained from Google Scholar and Publish or Perish, with inclusion criteria set on discussions of male participation in feminism. Thematic analysis was conducted to identify patterns, variations in findings, and research gaps. The results of this study show that the existence and involvement of male feminists are manifested in gender communities, educational campaigns, media presentations, and the dissemination of education on social media. Religiosity, particularly moderate Islam, is also a contextual factor that plays a role in men's involvement in the feminist movement. However, the existing literature is still dominated by studies on representation and does not explore the experiences and negotiations of men's identities. The findings in this study demonstrate that men's involvement is complex and contextual, so that a deeper and more critical empirical study is needed.   Abstrak. Gerakan feminisme bermula dari perlawanan perempuan terhadap ketidaksetaraan gender yang dalam perkembangannya turut melibatkan partisipasi laki-laki sebagai male feminist. Penelitian ini bertujuan untuk mengkaji eksistensi, perkembangan, bentuk partisipasi, dan makna keterlibatan male feminist di Indonesia. Penelitian ini menggunakan metode literature review terhadap enam artikel terpilih pada rentang tahun 2015-2024 yang didapatkan dari Google Scholar dan Publish or Perish, dengan penetapan kriteria inklusi pada pembahasan mengenai partisipasi laki-laki dalam feminisme. Analisis tematik dilakukan guna mengidentifikasi pola, varian temuan, dan celah penelitian. Hasil penelitian ini memperlihatkan bahwasannya eksistensi dan keterlibatan male feminist termanifestasi pada komunitas gender, kampanye edukasi, presentasi media, dan penyebaran edukasi di media sosial. Religiusitas, khususnya islam moderat turut menjadi faktor kontekstual yang berperan dalam keterlibatan laki-laki dalam gerakan feminisme. Akan tetapi, literatur yang ada masih didominasi oleh kajian mengenai representasi dan kurang mengeksplorasi pengalaman serta negosiasi identitas laki-laki. Temuan pada penelitian ini memperlihatkan bahwasannya keterlibatan laki-laki bersifat kompleks dan kontekstual, sehingga diperlukan kajian empiris yang lebih dalam dan kritis.